Hubungan faktor sosial ekonomi dengan kejadian LTFU terapi antiretroviral Pasien HIV/AIDS di klinik VCT sehati - Dau Wea, Margaretha Febianty; Dua Wida, Agustina Sisilia Wati; Vianitati, Pasionista (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2024)
Introduction: ARV therapy is crucial for the survival of person living with HIV/AIDS (PLWHA). As a result, PLWHA routinely visits VCT clinics to avoid losing track of them (LTFU). One of the factors influencing the presence of PLHIV in VCT clinics is socio-economics status. Objective: The research objective was to determine a correlation between socioeconomic factors and the occurrence of LTFU in ARV therapy. Method: This type of research employed quantitative with a cross-sectional approach. The population was 475 respondents and the sample was 35 respondents using accidental sampling. The data normality test used the Shapiro-Wilk test followed by the Chi-Square test to analyze the correlation. Results: The univariate test results revealed that the majority of PLWHA had lower socioeconomic factors, while the majority of LTFU were on antiretroviral therapy. The Chi-Square analysis obtained p value = 0.901 > a (0.05). indicating that H0 is accepted and Ha is rejected and that there is no correlation between socioeconomic factors and the incidence of loss to follow-up ARV therapy. Conclusion: There is no correlation between socioeconomic factors and the incidence of loss to follow up antiretroviral therapy at VCT Sehati clinic because it is supported by other influencing factors, namely family support, peer support, self efficacy and motivation. Keywords: AIDS, HIV, LTFU events, Socio-economic